Competing on capabilities – an analysis of supply chain flexibility in Australian manufacturing industry. (1st December 2006) - Kara, Sami; Kayis, Berman
In Australia, there has been an increasing need to improve the company's competitiveness in this world of global manufacturing. As a result, the main focus of this study is to investigate the extent of supply chain management practices adopted in the Australian manufacturing industry, based on an industrial survey covering 88 manufacturers. In this paper, we formulated possible relationships between several manufacturing parameters that may involve different flexibility elements in nine cases, in order to assess some weaknesses and strengths practiced by manufacturing industries in Australia. Several statistical analysis techniques were used to identify relationships as well as impediments for supply chain competitiveness.